2015
DOI: 10.1021/acs.inorgchem.5b01489
|View full text |Cite
|
Sign up to set email alerts
|

Periodicity, Electronic Structures, and Bonding of Gold Tetrahalides [AuX4] (X = F, Cl, Br, I, At, Uus)

Abstract: Systematic theoretical and experimental investigations have been performed to understand the periodicity, electronic structures, and bonding of gold halides using tetrahalide [AuX4](-) anions (X = F, Cl, Br, I, At, Uus). The [AuX4](-) (X = Cl, Br, I) anions were experimentally produced in the gas phase, and their negative-ion photoelectron spectra were obtained, exhibiting rich and well-resolved spectral peaks. As expected, Au-X bonds in such series contain generally increasing covalency when halogen ligands b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 89 publications
1
15
0
Order By: Relevance
“…Our results suggested that the I 2 − ions diffusion even occurred in dark conditions, might due to its low‐activation energy. Here, the charged AuI 2 − species do exist in a quasi‐linear complex with mixed valence states, suppressed the distribution of Au 3 − ions that could alter the work function and creates deep traps states that degrade the device stability . The mechanism of AuI 2 − formation and iodine diffusion is schematically represented in TOC.…”
Section: Resultsmentioning
confidence: 99%
“…Our results suggested that the I 2 − ions diffusion even occurred in dark conditions, might due to its low‐activation energy. Here, the charged AuI 2 − species do exist in a quasi‐linear complex with mixed valence states, suppressed the distribution of Au 3 − ions that could alter the work function and creates deep traps states that degrade the device stability . The mechanism of AuI 2 − formation and iodine diffusion is schematically represented in TOC.…”
Section: Resultsmentioning
confidence: 99%
“…Metal clusters have attracted much experimental and theoretical research interest in the past few decades. Certain clusters consisting of a metal atom surrounded by electronegative atoms can display “superatom” behavior . These clusters, also known as “superhalogens,” can possess electron affinities (EA) that are even larger than that of a Cl atom, which has the highest EA in the periodic table.…”
Section: Introductionmentioning
confidence: 99%
“…Certain clusters consisting of a metal atom surrounded by electronegative atoms can display "superatom" behavior. [1][2][3][4][5][6][7][8][9] These clusters, also known as "superhalogens," can possess electron affinities (EA) that are even larger than that of a Cl atom, which has the highest EA in the periodic table. Their size and composition can be controlled and they imitate the properties of an atom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An excellent review by Bellert and Breckenridge suggested that the XeAu + is described by a covalent bonding through an electrostatic model, while the nature of other NGAu + interactions is left undecided. Meanwhile, CM‐halides have also attracted many interests in terms of both experimental and theoretical investigations . Generally, the metal‐halides show ionic bonding characteristics.…”
Section: Introductionmentioning
confidence: 99%